UNDERSTANDING PROFILE FROM THE PHILOSOPHY, PRINCIPLES, AND CHARACTERISTICS OF RME - Julie, Hongki; Suwarsono, St.; Juniati, Dwi (Journal on Mathematics Education, 2014)
The aim of this study is to create understanding profiles of elementary school teachers who have been and have not been following the workshop PMRI, before and after they learned the learning resource about philosophy, principles, and characteristics of realistic mathematics approach. This type of research used in this study is a combination of qualitative research and developmental research. The results shown in this paper is the understanding profile of onesubject who is an elementary school teacher. Research subjects involved in the trial for the first task, the learning resource, and second task are six persons, which consists of three PGSD students who are working on the final project, and three elementary school teachers.Keywords: Understanding Profile, Realistic Mathematics Education (RME), the Realistic Mathematics Education Learning Resource. DOI: http://dx.doi.org/10.22342/jme.5.2.1499.148-159